Prevalence of excessive daytime sleepiness and its determinants among college students in Chengalpattu district, Tamil Nadu - R., Narendranath; Agadi, Soumya; I., Divya; A., Suriya Deva (International Journal of Research in Medical Sciences, 2022)
Background: Our body needs sleep for better functioning both physically and mentally. Sleep deprivation and daytime sleepiness are common problems related to sleep among the general population. College students are more prone to such problems. In this study, our aim is to assess the prevalence of daytime sleepiness among college students and to identify the factors responsible for the same. Methods: We conducted a cross-sectional study in the Chengalpattu district to assess the prevalence of excessive daytime sleepiness among college students from various courses including Architecture, Medical, and Para-medical students. A pre-tested, pre-designed, and modified questionnaire along with Epworth sleepiness scale (ESS) was used for data collection for the period of 3 months. The sample size we achieved was 422. Data analysis was done using SPSS version-22 software. Results: The prevalence of daytime sleepiness among our study participants were 32% (135) and most of them were facing sleep disturbances due to mobile and laptop usage, stress and overthinking, and other reasons like night studies, spending time with friends was 56% (76), 31% (42), 11% (14) respectively. Conclusions: Daytime sleepiness, disturbed sleep, inadequate sleep hygiene was highly prevalent among college students. It is creating various impacts on academics and driving. Disturbed sleep and EDS are caused by a host of reasons and have numerous negative impacts both physically and mentally. Irregular sleep schedules affect learning, memory, and performance, night studies may also affect the intrinsic aspects of sleep.